The effect of avocado butter to characteristics of emullient W/O cream - Teti Indrawati; Herlina Yuanita Sari (Indonesian Journal of Pharmacy, 2010)
Avocado butter is an unsafonifiable fraction of avocado oil that contains of 25-30  %  fitosterol  as  anti-aging  agent.  In  this  research,  the  influence  of  6 variation    avocado  butter  between  1–11 %  to  o/w  cream  characteristics  has been researched. O/W cream has been made by meltingand mixing methods at  700C,  and  than  cream  product  was  evaluated.  The  result showed  that  o/w cream  characteristics  were  progressively  influenced by  amount  of  avocado butter. In  using  avocado  butter  between  1–7  %  in  creams,  the  value  of    pH, viscosity,  and  particle  size  in  product  creams  progressively  go  down,  but  theirs spread-abilities progressively go  up. On the contrary cream characteristics that usage 9% of avocado butter, the value of viscosity and particle size began to go up while pH, but spread-abilities go down.Key words :avocado butter, O/W cream, cream characteristic, stability